Design Unmanned Minesweeper Catamaran as a Tool to Make a Safer Marine Environmental Using Analytical Methods - Kusuma, Cahya; Mulyono, Radityo Dimas; Kusdiana, Wawan; Syaifi, Muhammad; indiaryanto, Mahendra (International Journal of Offshore and Coastal Engineering (IJOCE), 2023)
After the war is over, the sea mine layer must be neutralized because if the mine explodes, it will cause environmental damage and the death of marine life. Minefields with very shallow water are difficult to clear using a minehunter. Mining in shallow sediment-covered areas is still hazardous, especially if the area is bridges, shore dredging, ports, or shipping lanes. This study designed the hull of the Unmanned Mines Sweeper (UMS) Catamaran, which towing side scan sonar so that it could double function as a mine-like detection and a survey vessel for seabed environmental conditions in very shallow areas. UMS design with analysis method using Maxsurf Modeler Advanced V21.13 software. Line plan design and general settings using AutoCAD software with data obtained from models designed using Maxsurf software. Total resistance value using Maxsurf Resistance Advanced V21.13 software. UMS uses a Catamaran design with an LoA of 4.823 meters, LwL of 4.177 m, and a width of 2.24 m. The ship has a high draft of 0.498 with a displacement of 1.557 tons. The results of the resistance analysis obtained Rt of 404.94 N. The drive system uses an electric motor that can provide endurance for 6 hours.